2015
DOI: 10.1109/tmag.2015.2450682
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Performance of Different Metal Foam Magnetorheological Fluid Materials

Abstract: SThe paper mainly investigates the dynamic response of different metal foam MR fluid materials experimentally. Metal foam magnetorheological (MR) fluid materials can be used to manufacture the low-cost controllable damping devices with needless of seal and long service life. MR fluid is stored in metal foam by the capillary force mainly.In the action of magnetic field, MR fluid will be extracted out from metal foam and fill up the shear gap, and then, produce the MR effect. Three types of metal foams with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…They were discovered with the aim to improve the mechanical strength over that of MRF impregnated sponges. Liu et al 413 described the dynamic response of different metal foam MRF materials. They used three types of metal foams: Fe, Ni and Cu.…”
Section: Other Mr Materialsmentioning
confidence: 99%
“…They were discovered with the aim to improve the mechanical strength over that of MRF impregnated sponges. Liu et al 413 described the dynamic response of different metal foam MRF materials. They used three types of metal foams: Fe, Ni and Cu.…”
Section: Other Mr Materialsmentioning
confidence: 99%
“…Jin et al studied the compression properties of magnetorheological elastomers with added different types and quantities of iron powder, and the experimental results showed that the compression modulus could be increased by 12% to 15% by applying a 300 mT magnetic field during the compression test, and the mechanical properties of magnetorheological elastomers improved with the increase of the applied magnetic field. Our previous research results also proved its good effect in the field of human knee joint vibration reduction. …”
Section: Introductionmentioning
confidence: 56%
“…It has been shown that in the presence of the magnetic field, the MR fluid is able to go out from the foam to make a contact with a surface that is placed not so far from the foam (up to 2 mm). Using this idea, an MR damper with a piston is proposed in [17][18][19], where the sponge is mounted at the housing wall over the circumference, and the electromagnet is attached to the moving piston. The principle sketch of this concept of MR damper is shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%